Corrigendum to “Phenotypic Detection of Metallo-β-Lactamase in Imipenem-ResistantPseudomonas aeruginosa” - Khosravi, Y.; Loke, M.F.; Chua, E.G.; Tay, S.T.; Vadivelu, J. (Hindawi Publishing Corporation, 2016)
The Acknowledgments section of the article titled “Phenotypic Detection of Metallo-β-Lactamase in Imipenem-Resistant Pseudomonas aeruginosa” [1] has been revised as follows: This paper is supported by University of Malaya-Ministry of Education (UM-MoE) High Impact Research (HIR) Grant UM.C/625/1/HIR/MoE/CHAN-02 (Account no. H-50001-A000013) and University of Malaya PPP Grant (Vote PS296/2007B). The authors would like to thank Professor Emeritus Yunsop Chong and Professor Kyungwon Lee from the Department of Clinical Pathology and Research Institute of Bacterial Resistance, Yonsei University College of Medicine, Seoul, Republic of Korea, for kindly providing the IMP-1, SIM-1, and VIM-2 β-lactamase producing Acinetobacter spp. and P. aeruginosa strains for use as positive controls.